Analysis of Biomechanical Gait Parameters in Patients after Total Hip Replacement in the Early Recovery Period - Dmitrii A. Somov; Marina R. Makarova; Egor A. Maiorov; Elena A. Turova; Nadezhda P. Lyamina (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2024)
INTRODUCTION. The widespread use of total hip arthroplasty (THA) places high demands on the restoration of a normal gait pattern and is one of the key goals of rehabilitation. AIM. Determination of key parameters of walking in patients after THA to assess the effectiveness of restoration of the physiological gait pattern. MATERIALS AND METHODS. In a control prospective study, the main group consisted of 23 patients (11 men, 12 women, aged from 41 to 75 years, mean age 63.9 ± 9.4 years), who in the first 8 weeks after planned THA, moved with the help of assistive devices. supports (two crutches or walkers) who underwent stage II of medical rehabilitation; control group - 27 healthy people (12 men and 15 women, aged from 42 to 73 years, average age 60.9 ± 9.9 years). Spatiotemporal and kinematic gait parameters were recorded before and after the rehabilitation course using a gait simulator with biofeedback equipped with three sensors. For each leg, spatiotemporal and kinematic biomechanical parameters were separately recorded. RESULTS. All spatiotemporal gait parameters on both limbs and pelvic mobility in the sagittal plane in patients in the early recovery period after THA before the start of the rehabilitation course are significantly different from healthy people. After a course of rehabilitation, the studied gait parameters approach physiological values. The main asymmetry is observed in the single support phase from 16 % at the beginning of the course, to 10 % at the end; sagittal pelvic mobility are 2 times higher than the physiological normal meaning at the beginning of the course, without significant changes in dynamics. DISCUSSION. Disturbances in the gait pattern are observed in the majority of patients undergoing THA. Step symmetry is one of the significant parameters of walking, according to which the primary global assessment of its quality is carried out. Asymmetry of the single support phase of the limbs is a natural development of compensatory motor reactions after endoprosthetics. CONCLUSION. The gait parameters "step frequency" and "step cycle" quickly change after a course of rehabilitation and can be used to assess the locomotor activity of patients during short courses of medical rehabilitation in the early recovery period. Indicators of stance and swing phases, their symmetry changes much more slowly, can serve as criteria for assessing the effectiveness of measures taken at the stages of rehabilitation in the dynamics of gait restoration.